Visionary Dances Ashton's Ballets of the Second World War - Morris, Geraldine (Edinburgh: Edinburgh University Press, 2008)
RESUMEN: Save for a cursory reference, art history tends to ignore dance and in particular the work made by Graham Sutherland and John Piper for the choreographer Frederick Ashton during the early 1940s. By overlooking dance and its designs, other than those for the Ballets Russes, the art world is wasting a valuable resource. In the following article I consider how the collaborations between Ashton, Sutherland and Piper illuminate the extent to which both the ballets and their designs were products not only of the circumstances of the 1939-1945 war but also, in particular, the propaganda of the period. This article considers how the particular discursive formations that shaped Ashton's ballets and the work of the artists led to dances and designs that were unique in both Ashton's output and that of the two painters.